The Role of Dynamic Pricing to Improve Revenue and Competitive Advantage (Maneggio, 2025)
Dynamic pricing is a pricing strategy that allows companies to adjust product prices based on demand, time, and customer behavior. With advances in technology and analytics, the application of this strategy is increasingly widespread, helping companies understand demand patterns in real-time and maximize revenue. Despite providing a competitive advantage, companies must pay attention to transparency and fairness in pricing in order to maintain customer trust. The implementation of dynamic pricing is expected to continue to evolve with the involvement of artificial intelligence and predictive analytics, allowing companies to set prices more accurately according to market conditions. In addition, dynamic pricing also plays a role in supporting sales of products that have a limited shelf life, so as to minimize waste and improve operational efficiency. This strategy also includes dynamic bundle pricing, which can increase customer loyalty through more relevant offers. The provision of discounts in this strategy contributes to an increase in positive interactions and product recommendations, although the impact is often temporary within the retail sector. Overall, dynamic pricing helps companies maintain competitiveness and improve customer satisfaction with more adaptive and data-driven pricing strategies.